Game Edukasi Pembelajaran Bahasa Inggris untuk Pengenalan Benda-Benda di Rumah bagi Siswa Kelas 4 Sekolah Dasar - Al Irsyadi, Fatah Yasin; Annas, Rifai; Kurniawan, Yogiek Indra (Jurnal Teknologi dan Informasi (JATI), 2019)
English has become one of the international languages ​​in this era. In the world of education, English lessons have been given since elementary school. "Madrasah Ibtidaiyah Al Islam Program Plus Dibal" is one of the schools that provides English language lessons for students in grade 4. One of the material provided is the introduction of objects in the house according to the 2013 curriculum. During the English learning activities in the classroom, the ability of some students to memorize vocabulary is still weak and the students' willingness to learn is low. The purpose of this study is to make an Android-based English education game application that can facilitate students in vocabulary recall and can increase students' willingness to learn. This study uses interviews with tutors at MI Al Islam Program Plus Dibal to collect data needed in the process of making educational games. This educational game was built using Construct 2 software as well as making game assets using CorelDraw X7. Testing is done by demonstrating the game in front of students and accompanied by teachers. After the application has been demonstrated, the game is played by students alternately, then students are given a questionnaire to test the performance and usability of the game. This game has 3 menus, namely 'Belajar' Menu, 'Kuis' Menu and 'Bermain' Menu. From the results of blackbox testing, it was found that the application was running well, in accordance with the expectations of the developer. From the test results of the User Acceptance Test, the average value of 'Strongly Agree' from the 5 statements given is 69.18% which shows a high level of acceptance from users of the application.